2015
DOI: 10.1016/j.molcel.2015.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Oscillation of Sulfiredoxin in the Mitochondria

Abstract: Hydrogen peroxide (H2O2) released from mitochondria regulates various cell signaling pathways. Given that H2O2-eliminating enzymes such as peroxiredoxin III (PrxIII) are abundant in mitochondria, however, it has remained unknown how such release can occur. Active PrxIII-SH undergoes reversible inactivation via hyperoxidation to PrxIII-SO2, which is then reduced by sulfiredoxin. We now show that the amounts of PrxIII-SO2 and sulfiredoxin undergo antiphasic circadian oscillation in the mitochondria of specific t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
109
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(118 citation statements)
references
References 22 publications
8
109
0
1
Order By: Relevance
“…We interpret the lower hydrogen peroxide in mitochondria upon hypoxia as prior mitochondrial release of H 2 O 2 into the cytosol, but it might as well reflect reduced mitochondrial production of H 2 O 2 under hypoxic conditions. A mitochondrial release of H 2 O 2 might also explain the increased nocturnal levels of Prx ox found after treatment with short term hypoxia, knowing that the release of mitochondrial H 2 O 2 into the cytosol is controlled by PrxIII, [44, 45], the abundance of which constitutes a large portion of the peroxiredoxin isoform pool [46]. In order to test the actual impact of altered cellular H 2 O 2 signaling on circadian time keeping we inhibited catalase, a major light-driven antioxidant enzyme regulating intracellular H 2 O 2 levels [47], with Amitrol and found that inhibition of the enzyme led to a lengthened period of the period1 gene oscillation in the zebrafish per1 luciferase reporter cell line DAP49 [48] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We interpret the lower hydrogen peroxide in mitochondria upon hypoxia as prior mitochondrial release of H 2 O 2 into the cytosol, but it might as well reflect reduced mitochondrial production of H 2 O 2 under hypoxic conditions. A mitochondrial release of H 2 O 2 might also explain the increased nocturnal levels of Prx ox found after treatment with short term hypoxia, knowing that the release of mitochondrial H 2 O 2 into the cytosol is controlled by PrxIII, [44, 45], the abundance of which constitutes a large portion of the peroxiredoxin isoform pool [46]. In order to test the actual impact of altered cellular H 2 O 2 signaling on circadian time keeping we inhibited catalase, a major light-driven antioxidant enzyme regulating intracellular H 2 O 2 levels [47], with Amitrol and found that inhibition of the enzyme led to a lengthened period of the period1 gene oscillation in the zebrafish per1 luciferase reporter cell line DAP49 [48] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given the known signaling role of H 2 O 2 , such a cyclic release of H 2 O 2 should alter in a timely fashion not only transcriptional clock regulators, many of which (such as REV-ERBb and the PER2:CRY1 heterodimer complex) are thiol-redox sensitive, but also the multitude of thiol-redox regulatory factors, as nuclear receptors, kinases, phosphatases, and transcription factors that are also or not involved in circadian regulation. In this regard, Kil et al (2015) show that activation of the p38 MAPK in the AG and BAT oscillates with a phase and period identical to that of PrxIII-SO 2 , which also indicates the oscillatory release of H 2 O 2 into the cytosol.…”
Section: Figure 2 Cyclic Reactivation Of Prxiii Upon Redox-dependentmentioning
confidence: 75%
“…If indeed this is the case, the presence of the PrxIII/Srx clockwork in AG, heart, and BAT, and not in the liver, might indicate a fundamental difference between the signals of food intake and physiological activity with regards to their integration by systemic clockwork mechanisms. Many other great questions are raised by the study of Kil et al (2015), such as the possible regulation of the PrxIII/Srx clockwork by PrxIII acetylation and phosphorylation, which are known to change its sensitivity to sulfinylation.…”
Section: Figure 2 Cyclic Reactivation Of Prxiii Upon Redox-dependentmentioning
confidence: 99%
See 2 more Smart Citations